Anthropogenic Influence of Sb in Tropical Soil and Effects to the Accumulation in Centella asiatica - Ong, Ghim Hock; Tan, A.L. (AENSI Publications, 2015)
Background: Large amount of plants in contaminated soils were found to accumulate high levels of antimony (Sb) in their edible parts, thereby causing potential risks to human health. In this study, the objectives were to assess the degree of anthropogenic influence of Sb in the soil and its accumulation in Centella asiatica based on the relationship of Sb concentrations in plant and soil. The soil and plant samples were collected from 12 sampling sites in Peninsular Malaysia. In order to confirm the effect of Sb concentrations in soil towards the plant, transplantation study was conducted under laboratory condition within one control site (UPM) and two potentially polluted site (Juru and Balakong). The levels of Sb present in soil and C. asiatica were analysed with Instrumental Neutron activation analysis (INAA). Sb concentration in soils from the 12 sampling sites in Peninsular Malaysia were ranged from 2.21 μg/g to 5.10 μg/g. Based on enrichment factor (EF) and index of geoaccumulation (Igeo), Sb levels in Peninsular Malaysia were in mild polluted level. The range of Sb in roots were from 0.64 μg/g to 1.61μg/g while 0.22 μg/g to 0.49 μg/g in shoots. Sb levels were found to be highest in roots followed by shoots in C. asiatica. Based on the results from the transplantation study, high translocation factor (TF) values indicated high Sb level been translocated from roots to shoots but low BCF values showed low Sb uptake from soil to roots. Overall, Sb pollution in Peninsular Malaysia was considered mild based on Ef and Igeo values. Hence, we can conclude that Sb levels in C. asiatica from Peninsular Malaysia were not harmful for human consumption.